2016
DOI: 10.1007/s10534-016-9937-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro heme biotransformation by the HupZ enzyme from Group A streptococcus

Abstract: In Group A streptococcus (GAS), the metallorepressor MtsR regulates iron homeostasis. Here we describe a new MtsR-repressed gene, which we named hupZ (heme utilization protein). A recombinant HupZ protein was purified bound to heme from Escherichia coli grown in the presence of 5-aminolevulinic acid and iron. HupZ specifically binds heme with stoichiometry of 1:1. The addition of NADPH to heme-bound HupZ (in the presence of cytochrome P450 reductase, NADPH-regeneration system and catalase) triggered progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 73 publications
(125 reference statements)
0
33
0
Order By: Relevance
“…Currently only apo-crystal structures exist for HutZ and HupZ, but analyses using single site substitution mutagenesis of HutZ have shown that His63 and Arg92 (corresponding to His245 and Arg166 in HugZ) interact with the propionate due to shifts in heme-bound spectra (Liu X. et al, 2012 ). HupZ, however, lacks His245 and contains a glycine instead of Arg166, making it difficult to determine the heme coordinating residues based on sequence analysis alone (Sachla et al, 2016 ). Interestingly, ChuZ crystallized not only with the expected heme binding site, but with an additional surface bound heme molecule (Zhang et al, 2011 ).…”
Section: The Structure and Function Of Heme Degrading Enzymesmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently only apo-crystal structures exist for HutZ and HupZ, but analyses using single site substitution mutagenesis of HutZ have shown that His63 and Arg92 (corresponding to His245 and Arg166 in HugZ) interact with the propionate due to shifts in heme-bound spectra (Liu X. et al, 2012 ). HupZ, however, lacks His245 and contains a glycine instead of Arg166, making it difficult to determine the heme coordinating residues based on sequence analysis alone (Sachla et al, 2016 ). Interestingly, ChuZ crystallized not only with the expected heme binding site, but with an additional surface bound heme molecule (Zhang et al, 2011 ).…”
Section: The Structure and Function Of Heme Degrading Enzymesmentioning
confidence: 99%
“…In vitro degradation of heme by HugZ, ChuZ, and HupZ was observed in the presence of catalase (Ridley et al, 2006 ; Guo et al, 2008 ; Sachla et al, 2016 ). All three proteins degrade heme to produce CO and a chromophore that absorbs at 660 nm (in the presence of ascorbate or CPR/NADH).…”
Section: The Structure and Function Of Heme Degrading Enzymesmentioning
confidence: 99%
See 3 more Smart Citations